Institutional Diversity in China - Hayhoe, Ruth; Li, Jun (International Higher Education, 2012)
This article explains how diversity has been maintained in spite of the homogenizing pressures of globalization on Chinese higher education. As a result of national policy and institutional initiative, normal universities, agricultural universities and universities focusing on minority cultures have maintained their unique identities.